The Influence of Humility and Forgiveness on Bullying Behavior in Islamic Student (G-Couns: Jurnal Bimbingan dan Konseling, 2024)
Islamic boarding schools use a disciplinary system designed to make students accountable for their behavior. On the other hand, certain supervisors, also known as mudabbir or mudabbirah, could abuse it in order to threaten or exact revenge on students. Strict regulations and insufficient oversight create a climate that encourages bullying. Elliott's (2010) humility scale, McCullough et al TRIM-18 scale (adapted by Agung (2015)), and Shaw et al.'s (2013) bullying scale (FBS) were among the measurement instruments used. According to regression analysis, forgiveness greatly decreased bullying (p = 0.033), whereas humility did not significantly reduce bullying (p = 0.431). The entire regression model's lack of significance (p = 0.088) implies that differences in bullying behavior may not be significantly impacted by attitudes toward humility and forgiveness. This study investigates the relationship between bullying among Islamic boarding school students and attitudes of humility and forgiveness. Keywords: bullying, humility, forgiveness, islamic boarding school